Detecting miRNA biomarkers from extracellular vesicles for cardiovascular disease with a microfluidic system12. Issue 19 (17th August 2018) - Cheng, Hong-Lin; Fu, Chien-Yu; Kuo, Wen-Che; Chen, Yen-Wen; Chen, Yi-Sin; Lee, Yung-Mao; Li, Kuang-Hsien; Chen, Chihchen; Ma, Hsi-Pin; Huang, Po-Chiun; Wang, Yu-Lin; Lee, Gwo-Bin
Abstract : A novel microfluidic platform for extracellular vesicle extraction, microRNA isolation and detection with field-effect transistors for early detection of cardiovascular diseases. Abstract : According to World Health Organization reports, cardiovascular diseases (CVDs) are amongst the major causes of death globally and are responsible for over 18 million deaths every year. Traditional detection methods for CVDs include cardiac computerized tomography scans, electrocardiography, and myocardial perfusion imaging scans. Although diagnosis of CVDs through such bio-imaging techniques is common, these methods are relatively costly and cannot detect CVDs in their earliest stages. In contrast, the levels of certain micro RNA (miRNA) biomarkers extracted from extracellular vesicles (EVs) in the bloodstream have been recognized as promising indicators for early CVD detection. However, detection and quantification of miRNA using existing methods are relatively labor-intensive and time-consuming. In this study, a new integrated microfluidic system equipped with highly sensitive field-effect transistors (FETs) was capable of performing EV extraction, EV lysis, target miRNA isolation and miRNA detection within 5 h. The limit of detection was within the physiological range (femtomolar) for two targeted miRNAs, miR-21 and miR-126, meaning that this integrated microfluidic system has the potential to be used as a tool for early detection of CVDs.